2019
DOI: 10.3390/su11247200
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Coastal Agriculture under Climate Change

Abstract: Climatic and non-climatic stressors, such as temperature increases, rainfall fluctuations, population growth and migration, pollution, land-use changes and inadequate gender-specific strategies, are major challenges to coastal agricultural sustainability. In this paper, we discuss all pertinent issues related to the sustainability of coastal agriculture under climate change. It is evident that some climate-change-related impacts (e.g., temperature and rainfall) on agriculture are similarly applicable to both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 146 publications
(174 reference statements)
0
52
0
Order By: Relevance
“…Since salinity is a major abiotic stress that is expected to impact negatively on an estimated 50% of all arable soils worldwide by 2050 (47), our work suggests that global food production could be improved by selecting for RSAs that can avoid the damage caused by saline conditions (10). Saltwater intrusions and waterlogging in coastal regions due to sea level rise and cyclones, which will be exacerbated by climate change, threaten crop productivity worldwide (48). In the case of paddy rice, which is a staple food in those swampy regions, qsor1 could prove to be a valuable breeding target to improve yields in saline paddy fields.…”
Section: Discussionmentioning
confidence: 93%
“…Since salinity is a major abiotic stress that is expected to impact negatively on an estimated 50% of all arable soils worldwide by 2050 (47), our work suggests that global food production could be improved by selecting for RSAs that can avoid the damage caused by saline conditions (10). Saltwater intrusions and waterlogging in coastal regions due to sea level rise and cyclones, which will be exacerbated by climate change, threaten crop productivity worldwide (48). In the case of paddy rice, which is a staple food in those swampy regions, qsor1 could prove to be a valuable breeding target to improve yields in saline paddy fields.…”
Section: Discussionmentioning
confidence: 93%
“…The majority of the existing studies on coastal agricultural vulnerability focus on other parts of the world [13,25,56]. Further, the limited existing work on coastal agricultural vulnerability both in India [14,15] and globally [18,25] seldom uses primary data and a combination of qualitative, quantitative and spatial methods. Second, much of the existing literature on both agricultural vulnerability [36,41,42] and coastal vulnerability [52,57] tend to neglect to analyse a combination of climatic and social perspectives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As shown in Figure 13, more than 48 percent of cells were rated as having very high vulnerability (19)(20)(21)(22)(23)(24), and 19 percent of the cells were rated as highly vulnerable (16)(17)(18). In addition, only six percent of the cells were found to be moderately vulnerable (12)(13)(14)(15). The overall CVI scores clearly indicated that 67 percent of cells have either extremely high or high agricultural vulnerability in the selected 22 case study areas in Coastal Andhra Pradesh (Krishna and Guntur districts).…”
Section: Overall Agcvi Scores and Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have also found that a number of human resettlements established after the civil war were in areas very close to the coast. This increasing population along the coastal fringes of Jaffna Peninsula will further increase the vulnerability of the paddy lands in the coastal lowlands to salinization [55]. The subsequent construction of more new wells and the over-extraction of groundwater is likely to increase seawater intrusion into coastal aquifers [27].…”
Section: Discussionmentioning
confidence: 99%